ENTERPRISE ARCHITECTURE SISTEM PENJUALAN DENGAN METODE TOGAF ADM PADA DEKRANASDA KABUPATEN PRINGSEWU - Marsilia, Vita (YHMM PUBLISHING, 2023)
Enterprise architecture is a picture of a combination of several business processes, the information needed, along with the technology that supports the business. Dekranasda Pringsewu Regency is the Crafts and Arts Council which sells various kinds of handicrafts from craftsmen in the Pringsewu district area. The purpose of this study was to design a website-based sales application system at Dekranasda Pringsewu Regency, which previously used a conventional system. The methodology used in creating the enterprise architecture model is TOGAF ADM (Architecture Development Method). The research was carried out by observation, interviews and documentation related to the current conditions of business processes, information systems and infrastructure. The implementation of the application is running well and as it should so that it can meet the information and business needs of Dekranasda Pringsewu Regency.